MEMBANGUN MEDIA PEMBELAJARAN 7 KEAJAIBAN DUNIA BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS VI - Akbar Permana Putra; Tri Widodo; Tri Rochmadi (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2019)
Educational Equity in Indonesia is categorized low, it is approved by decreased amount of facilities used in learning process. There are finded in only particular sectors like city, then in village and minorities have not been got the same right. The using of learning media is so helpful in delivering the material among to the students and can be used as dynamic teaching material so it can help in catching and understanding the material. Augmented reality is one of technological development that can be used in making learning media in android operation system with using marker as object reader such as seven wonders of the world. The using of augmented reality makes the object more factual so it can increase students’s motivation in learning. The method used in making this media is Systems Development Life Cycle method followed as 1) Analysis, 2) Design, 3) Testing, 4) Implementation and 5) Maintenance. Testing in making learning media application seven wonders of the world is applied with using black box testing and media expert, material expert and users’s testing. The testing result presents this media can help teaching learning process with percentage average is 90.37 % got from media expert’s testing in 86,36%, material expert’ testing in 87,5%, and user’s testing in 97,27%. It means this learning media is so practiced.